Effectiveness of the self-tapping relaxation technique on dysmenorrhea pain among nursing students - Veronica Silalahi; Irine Yunila Prastyawati (Malahayati International Journal of Nursing and Health Science, 2022)
Background: Menstruation is the discharge of blood, mucus, and cell debris from the uterus at regular intervals with a regular cycle. One of the non-pharmacological methods that can be used to reduce menstrual pain is self-tapping. The phenomenon found in female students of the Emmaus Dormitory in Surabaya, they overcome dysmenorrhea by taking anti-pain medication, consuming traditional herbal medicine " turmeric/curcuma terra merita (meritorious earth) " and not being given anything until the pain goes away.Purpose: To analyse the effectiveness of the self-tapping relaxation technique on dysmenorrhea painMethod: One-group-pre-post test experimental design with a population of nursing students living in the Emmaus female dormitory in Surabaya who experienced primary dysmenorrhea. The sampling technique used was simple random sampling with 35 participants. The instrument used is the Numeric Rating Scale.Results: In the self-tapping pre-intervention, most of the participants (51%) experienced severe pain. After being given self-tapping more than 50% (51%) of the participants experienced mild pain. Wilcoxon test results showed = 0.05 and p = 0.000. p-value < then Ho is rejected, which means that there is an effect of self-tapping on the decrease in the level of primary dysmenorrhea.Conclusion : Self-tapping techniques can reduce primary dysmenorrhea by increasing the serotonin hormone.